Silencing sensory neuron membrane protein RferSNMPu1 impairs pheromone detection in the invasive Asian Palm Weevil - Johny, Jibin; Nihad, Mohammad; Alharbi, Hattan A; AlSaleh, Mohammed Ali; Antony, Binu (Scientific reports, 2024)
The red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier), also known as the Asian palm weevil, is an invasive pest that causes widespread damage to palm trees around the globe. As pheromone communication is crucial for their mass attack and survival on palm trees, the olfactory concept of pest control strategies has been widely explored recently. We aim to understand the molecular basis of olfaction in RPW by studying one of the key olfactory proteins in insect pheromone communication, sensory neuron membrane proteins (SNMPs). SNMPs belong to the CD36 (cluster of differentiation 36) family that perform two distinct olfactory roles in insects, either in pheromone (odorant) transfer to the odorant receptors (SNMP1) or in the pheromone clearing process (SNMP2). In this study, we performed antennal transcriptomic screening and identified six SNMPs, mapping them on the R. ferrugineus genome, and confirmed four distinct SNMPs. Both SNMP1 proteins in RPW, viz., RferSNMPu1 and RferSNMPu2, were mapped onto the same scaffold in different loci in the RPW genome. To further understand the function of these proteins, we first classified them using phylogenetic analysis and checked their tissue-specific expression patterns. Further, we measured the relative transcript abundance of SNMPs in laboratory-reared, field-collected adults and pheromone-exposure experiments, ultimately identifying RferSNMPu1 as a potential candidate for functional analysis. We mapped RferSNMPu1 expression in the antennae and found that expression patterns were similar in both sexes. We used RNAi-based gene silencing to knockdown RferSNMPu1 and tested the changes in the RPW responses to aggregation pheromone compounds, 4-methyl-5-nonanol (ferrugineol) and 4-methyl-5-nonanone (ferrugineone), and a kairomone, ethyl acetate using electroantennogram (EAG) recordings. We found a significant reduction in the EAG recordings in the RferSNMPu1 knockdown strain of adult RPWs, confirming its potential role in pheromone detection. The structural modelling revealed the key domains in the RferSNMPu1 structure, which could likely be involved in pheromone detection based on the identified ectodomain tunnels. Our studies on RferSNMPu1 with a putative role in pheromone detection provide valuable insight into understanding the olfaction in R. ferrugineus as well as in other Curculionids, as SNMPs are under-explored in terms of its functional role in insect olfaction. Most importantly, RferSNMPu1 can be used as a potential target for the olfactory communication disruption in the R. ferrugineus control strategies.
Keywords: Male; nosatcovití; Animals; Gene Silencing; receptory pachové; tykadla členovců; RNAi; Receptors, Odorant; Palm weevil; mužské pohlaví; Female; Sensory neuron membrane protein; Insect Proteins; Olfaction; Pest control; hmyzí proteiny; Electrophysiology; feromony; Membrane Proteins; ženské pohlaví; umlčování genů; zvířata; membránové proteiny; fylogeneze; Arthropod Antennae; Sensory Receptor Cells; nervové receptory; Weevils; Phylogeny; Pheromones